Quality of life in people with coronary artery disease: translation and cross-cultural adaptation of a questionnaire - Ana Raquel Viegas de Assis; Luize Maximo e Melo; Vinícius Batista Santos; Juliana de Lima Lopes (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to carry out translation, cross-cultural adaptation to Portuguese and assess the reliability of the four versions of the Coronary Revascularization Outcome Questionnaire - adapted. Methods: a methodological study of translation and cross-cultural adaptation into Portuguese, as proposed by Beaton et al., and reliability analysis, by calculating Cronbach's alpha coefficient and item-total correlation of the four versions of the Coronary Revascularization Outcome Questionnaire - adapted. Results: the adaptations made facilitated the understanding of the items. All domains had Cronbach's alpha above 0.70, except two in the post-percutaneous coronary intervention version and two in the post-myocardial surgical revascularization version. All items had item-total correlation values greater than 0.20, except two in the post-percutaneous coronary intervention version, one in the pre-coronary intervention version and six in the post-myocardial surgical revascularization version. Conclusion: the cross-cultural adaptation to Portuguese was considered satisfactory. Pre-procedure versions were considered reliable, while the post-procedures require other psychometric analyses.